Visceral Leishmaniasis as a Possible Reason for Pancytopenia - Koster, Kira-Lee; Laws, Hans-Jürgen; Troeger, Anja; Meisel, Roland; Borkhardt, Arndt; Oommen, Prasad Thomas (Frontiers in Pediatrics, 2015)
Leishmaniasis is caused by different species of the protozoa Leishmania and frequently found in South-Western Asia, Eastern Africa, Brazil and Mediterranean countries. Leishmania are transmitted to humans by the bite of sandflies. After weeks to months, unspecific symptoms may occur, accompanied by more specific findings like pancytopenia and organomegaly. We report two children with pancytopenia and hepato-/splenomegaly: A 1-year-old boy first diagnosed with an Adenovirus-infection, accompanied by fever, pancytopenia and hepatosplenomegaly who had spent his summer vacation in Spain and a 3-year-old boy of Macedonian origin who was first diagnosed with a Parvovirus B19-infection again accompanied by splenomegaly and pancytopenia. In both children leukemia was excluded by an initial bone marrow puncture. As fever was still persistent weeks after the childrens’ first hospital stay, both children received antibiotics empirically without sustainable effect. While different autoantibodies were present in both children, an immunosuppressive therapy was initiated in the younger boy without therapeutic success. A second bone marrow puncture was performed and Leishmania were finally detected morphologically and proven serologically. After weight-adjusted treatment with liposomal Amphotericin B for 10 days, both children recovered completely without relapse. Aim of this report is to broaden the spectrum of differential diagnoses in children with pancytopenia, splenomegaly and fever to visceral leishmaniasis particularly when travel history is positive for the Mediterranean area. The infection may mimic more common diseases such as leukemia, viral infections or autoimmune diseases because polyclonal B cell activation and other mechanisms may lead to multiple positive serologic tests. Both cases illustrate typical pitfalls and shall encourage to taking Leishmaniasis into diagnostic consideration.